Digital dead end : fighting for social justice in the information age - Eubanks, Virginia (Cambridge, Mass. : MIT Press, 2011)
Includes bibliographical references and index. Four beginnings -- The real world of information technology -- Trapped in the digital divide -- Drowning in the sink-or-swim economy -- Technologies of citizenship -- Popular technology -- Cognitive justice and critical technological citizenship.